Agenda and Goals for a Meeting of Oxnard Delegation with Representatives of the Chancellor of California Community Colleges (1974)
The agenda and goals of a meeting held between Oxnard Delegation and Representatives of the Chancellor of California Community Colleges. Discusses the role of the Chancellor's office and aims to learn of what information needs to be provided in order to obtain support for the development of Oxnard Community College.